Mexico: industrial policies and the production of information and communication technology goods and services - Claudia Schatan; Leobardo Enríquez (CEPAL Review, 2015)
This study investigates the extent to which the digital boom has had repercussions on productive activity, in terms of both manufacturing (ict goods) and services (ict services), in addition to its potential ramifications in the rest of the Mexican economy. Input-output matrices are used and compared to those of Brazil and the United States. Mexico has fallen behind, particularly in the production of ict goods, and the productive chains of this activity have weakened. The ict services sector offers much greater potential than has been exploited thus far, with the advantage that it involves comparatively more value added and has major diversification possibilities. It is considered essential to find more effective industrial policies targeted on the ict goods and services sectors; but the experience of countries such as Brazil, which have applied more proactive approaches with mixed results, suggests that this will be challenging.